Le portrait journalistique: reflet de soi ou genre en soi? L’exemple du portrait d’analphabète dans une presse francophone au Canada - Arrighi, Laurence (Ponti/Ponts, 2021)
In journalistic discourse, individual profiles are used as examples of more general social phenomena. They personify social problems. The profile genre is both strongly codified and generally serves to underline an existing vision of things, rather than pushing the analysis in new directions. The profiles of illiterate individuals in the New Brunswick (Canada) French-language daily newspaper, l’Acadie Nouvelle, analysed within the context of all articles on illiteracy, shows that profiles entirely reproduce the same journalistic discourse found in news articles, interviews with experts and other journalistic genres. In this text I summarise the strict rules governing these profiles, ponder their usefulness and analyze the consequences of what the profiles both claim to demonstrate and end up concealing.